Membangun Ketahanan Organisasional: Peran Kepemimpinan dan Komunikasi dalam Menghadapi Perubahan Tinjauan Sistematic Literature Review - Calipah, Ilah; Mustofa, Jeni; Fitriani, Lili Karmela (LPPM Institut Pendidikan Nusantara Global, 2024)
In an era, full of rapid and unpredictable change, organizational resilience is the key to survival and development. An organization's ability to adapt to change and overcome challenges is an important factor in achieving long-term success. An organization's ability to adapt and develop amidst change is the main key to achieving organizational resilience. In this context, leadership and communication play a crucial role. This research conducted a systematic review of the literature to explore the role of leadership and communication in building organizational resilience amidst change. This review identifies various factors of effective leadership and communication strategies and practices in dealing with change, and discusses the challenges and obstacles that may be encountered. Effective leadership and communication are critical to building organizational resilience amidst change. By implementing the right strategies and practices, organizations can improve their ability to adapt and thrive in a dynamic environment.